2012
DOI: 10.1002/pmic.201100499
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid top‐down proteomics evidenced the potential biomarker role of LVV‐ and VV‐hemorphin‐7 in posterior cranial fossa pediatric brain tumors

Abstract: Posterior cranial fossa is the most frequent location of pediatric brain tumors. Its diagnosis is currently performed by postsurgery histopathology and the identification of biomarkers in cerebrospinal fluid (CSF) could provide a less invasive tool. Patient CSF was collected during surgery before the tumor removal (PRE-CSF) and 6 days after the resection (POST-CSF) and analyzed by top down LC-MS proteomics for comparison. The PRE-CSFs generally exhibited a less complex LC-MS profile than the relative POST-CSFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Specifically, in relation to the latter, the expression of both opioid receptors and their ligands in tumor cells suggested their role in tumor progression [40]. Additionally, non-classical opioid peptides, the hemorphins, were reported in our previous paper as potential biomarkers of prognosis in posterior fossa pediatric brain tumor cerebrospinal fluid [41].…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, in relation to the latter, the expression of both opioid receptors and their ligands in tumor cells suggested their role in tumor progression [40]. Additionally, non-classical opioid peptides, the hemorphins, were reported in our previous paper as potential biomarkers of prognosis in posterior fossa pediatric brain tumor cerebrospinal fluid [41].…”
Section: Discussionmentioning
confidence: 94%
“…Phosphorylated proteoforms of cardiac troponin I have been identified as candidate biomarkers for chronic heart failure by FTICR-MS (109). Orbitrap-based instrumentation has been applied to intact biomarker studies that have identified candidate proteoform biomarkers in cerebrospinal fluid for pediatric brain tumor prognosis (110) as well as multiple salivary proteoforms potentially associated with complications of Down syndrome, including early onset Alzheimer’s disease (111). Additionally, TDP has been applied to biomarker studies concerning cirrhosis at risk of malignancy (ubiquitin PTMs) (112), schizophrenia and bipolar disorder (113), neurodevelopmental disorders (in combination with MALDI MS imaging) (114), Parkinson’s disease (alpha-synuclein proteoforms) (115), and medulloblastoma and pilocytic astrocytoma (116), all in just the past two years.…”
Section: Conclusion: the Power And Promise Of The Proteoformmentioning
confidence: 99%
“…More recently, capillary electrophoresis has allowed separation of intact proteins and peptides in small capillaries under high voltage, using low sample and reagent consumption, and with high efficiency [131]. Some of these approaches, called top-down proteomics, although less employed than bottom-up proteomics, have shown their usefulness in investigating disease biomarkers [132][133][134][135][136][137][138][139]. They have been described as a complementary cost-effective approach in clinical research [140], and recently promoted by a new consortium for the comprehensive analysis of intact proteins [www.topdownproteomics.org.…”
Section: Proteomics Approach For Intact Proteinsmentioning
confidence: 99%